2010
DOI: 10.1080/03075070903383211
|View full text |Cite
|
Sign up to set email alerts
|

‘It’s almost a mindset that teachers need to change’: first‐year students’ need to be inducted into time management

Abstract: This article discusses the findings related to a number of research projects investigating students' expectations and experiences of the first year in higher education. In particular, findings with regard to first-year students' expectations and challenges with issues of time management are reported. It was found that many students were realistic about having to plan their work independently, and having to spend a good amount of their time during the week on self-study. However, many students found it difficul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
78
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(84 citation statements)
references
References 19 publications
3
78
0
3
Order By: Relevance
“…This tendency (or lack thereof ) was often based on the student's ability (or inability) to estimate academic rigor realistically. Vandermeer, Jansen, and Torenbeek (2004) found that students who accurately predicted the difficulty of college level work were more likely to succeed, and Wyatt, Saunders, and Zelmer (2005) found that faculty felt that college students consistently underestimated the amount of effort that would be necessary in order for the students to do well in college classes. However, as Meyer, Spencer, and French (2009) point out, research on college students' perceptions of academic rigor is rare, thus making connections between perceptions, effort, and outcome difficult to achieve.…”
Section: Managing Free Time and The Dangers Of Underestimating Academmentioning
confidence: 99%
See 1 more Smart Citation
“…This tendency (or lack thereof ) was often based on the student's ability (or inability) to estimate academic rigor realistically. Vandermeer, Jansen, and Torenbeek (2004) found that students who accurately predicted the difficulty of college level work were more likely to succeed, and Wyatt, Saunders, and Zelmer (2005) found that faculty felt that college students consistently underestimated the amount of effort that would be necessary in order for the students to do well in college classes. However, as Meyer, Spencer, and French (2009) point out, research on college students' perceptions of academic rigor is rare, thus making connections between perceptions, effort, and outcome difficult to achieve.…”
Section: Managing Free Time and The Dangers Of Underestimating Academmentioning
confidence: 99%
“…While the value and importance of effective time management have received a good amount of attention in the higher education research literature (Vandermeer, Jansen, & Torenbeek, 2004), Goleman's (1995) groundbreaking work on emotional intelligence closely reflects how the students in the study effectively managed both themselves and their time.…”
Section: Managing Free Time and The Dangers Of Underestimating Academmentioning
confidence: 99%
“…Five studies examined the time management behaviors and practices of specific populations using qualitative methodologies including the use of time diaries (Hessing, 1994;Ho, 2003;Kotter, 1980;Winter et al, 1993;Yoels & Clair, 1994). Twenty-seven studies examined time management behaviors or practices in relation to other variables such as academic achievement, stress, or creativity (Adams & Jex, 1997Alay & Koçak, 2002;Anand, 2007;Britton & Tesser, 1991;Burt & Kemp, 1994;Cemaloglu & Filiz, 2010;Claessens et al, 2004;Francis-Smythe & Robertson, 1999;Garcia-Ros et al, 2004;Hellsten & Rogers, 2009;Jex & Elacqua, 1999;Lahmers & Zulauf, 2000;Lang et al, 1990;Lay & Schouwenburg, 1993;Macan et al, 1990;Misra & McKean, 2000;Mpofu et al, 1996;Mudrack, 1997;Shahani et al, 1993;Simons & Galotti, 1992;Swart et al, 2010;Trockel et al, 2000;van de Meer, et al, 2010;Williams et al, 1995;Zampetakis et al, 2010). One study (Trueman & Hartley, 1996) compared the effectiveness of time management skills between mature and traditional entry university students.…”
Section: Empirical Studies Of Time Managementmentioning
confidence: 99%
“…Recent time management training programs are also taking advantage of technology for their delivery (e.g., Zinatelli et al, 2002). The focus of time management research has also expanded to include individuals from North America (e.g., Hellsten & Rogers, 2009), Europe (Garcia-Ros et al, 2004van de Meer et al, 2010;Zampetakis et al, 2010), Africa , and Australia (Kearns & Gardnier, 2007) and is cross-cultural in nature (e.g., Cemaloglu & Filiz, 2010;Garcia-Ros et al, 2004).…”
Section: Who Uses Time Management?mentioning
confidence: 99%
“…Their results indicated that students perceived the importance or non-relevance of developing specific skills (e.g., writing, problem-solving) in relation to their future professional identities. Van der Meer, Jansen, and Torenbeek (2010) used survey and interview data with approximately 2000 first-year students across two research sites. Time management was identified as a significant challenge for many students.…”
Section: Introductionmentioning
confidence: 99%